Engineering applications of neural networks : 18th International Conference, EANN 2017, Athens, Greece, August 25-27, 2017, Proceedings /: 18th International Conference, EANN 2017, Athens, Greece, August 25-27, 2017, Proceedings. (2017) - Unknown
No abstract available